Adjuvant sunitinib following chemoradiotherapy and surgery for locally advanced esophageal cancer: a phase II trial. Issue 8 (10th December 2015) - Horgan, A. M; Darling, G.; Wong, R.; Guindi, M.; Liu, G.; Jonker, D. J.; Lister, J.; Xu, W.; MacKay, H. M.; Dinniwell, R.; Kim, J.; Pierre, A.; et al.
Summary: The prognosis for locally advanced esophageal cancer is poor despite the use of trimodality therapy. In this phase II study, we report the feasibility, tolerability and efficacy of adjuvant sunitinib. Included were patients with stage IIa, IIB or III cancer of the thoracic esophagus or gastroesophageal junction. Neoadjuvant therapy involved Irinotecan (65 mg/m 2 ) + Cisplatin (30 mg/m 2 ) on weeks 1 and 2, 4 and 5, 7 and 8 with concurrent radiation (50Gy/25 fractions) on weeks 4–8. Sunitinib was commenced 4–13 weeks after surgery and continued for one year. Sixty‐one patients were included in the final analysis, 36 patients commenced adjuvant sunitinib. Fourteen patients discontinued sunitinib due to disease recurrence (39%) within the 12‐month period, 12 (33%) discontinued due to toxicity, and 3 (8%) requested cessation of therapy. In the overall population, median survival was 26 months with a 2 and 3‐year survival rate of 52% and 35%, respectively. The median survival for the 36 patients treated with sunitinib was 35 months and 2‐year survival probability of 68%. In a historical control, a prior phase II study with the same trimodality therapy ( n = 43), median survival was 36 months, with a 2‐year survival of 67%. Initiation of adjuvant sunitinib is feasible, but poorly tolerated, with no signal of additional benefit over trimodality therapy for locally advanced esophageal cancer.